2021
DOI: 10.3389/fmars.2021.773367
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Trophic Niches in Mobile Epifauna Assemblages Associated With Seaweeds and Habitats of Syngnathid Fishes in Cíes Archipelago (Atlantic Islands Marine National Park, North West Iberia)

Abstract: Syngnathids are vulnerable fishes closely associated with seaweeds and seagrass, which provide shelter and food resources. Even though most syngnathids commonly feed on small crustaceans, the feeding regimes may differ depending on the species and prey availability. This is the first monitoring study to explain syngnathid abundances and dietary regimes within macroalgal beds in Cíes Archipelago (Atlantic Islands Marine National Park, North West Iberian Peninsula). We sampled the epifaunal assemblages in seawee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 137 publications
2
35
0
Order By: Relevance
“…Simultaneously to fish monitoring, samples of potential prey for S. acus were collected in the same sampling sites of this study for further identification and stable isotope analysis [14].…”
Section: Study Sitesmentioning
confidence: 99%
See 4 more Smart Citations
“…Simultaneously to fish monitoring, samples of potential prey for S. acus were collected in the same sampling sites of this study for further identification and stable isotope analysis [14].…”
Section: Study Sitesmentioning
confidence: 99%
“…Due to the low lipid content in the fin samples conserved in ethanol (<5% lipids, C:N < 3.56) [44,45], normalization for lipid correction in the fin samples was not necessary [37,46]. However, the C:N values in the epifauna indicated that the lipid content was higher than 5%, and specific conversion factors constructed for lipid normalization were applied [14]. Additionally, some epifaunal groups were submitted to acidification before SIA [14] by adding dilute (10%) HCl drop-by-drop, until CO 2 release was no longer observed [47,48].…”
Section: Stable Isotopes Analysis (Sia)mentioning
confidence: 99%
See 3 more Smart Citations